Sustainable biorefinery approaches towards circular economy for conversion of biowaste to value added materials and future perspectives. (1st October 2022) - Duan, Yumin; Tarafdar, Ayon; Kumar, Vinay; Ganeshan, Prabakaran; Rajendran, Karthik; Shekhar Giri, Balendu; Gómez-García, Ricardo; Li, Huike; Zhang, Zengqiang; Sindhu, Raveendran; Binod, Parameswaran; Pandey, Ashok; et al.
Graphical abstract: Highlights: Sustainable development and resource recovery from biowaste is review. Comprehensive explained biowaste treatment technology. Introduce the public participate in implement waste reduce and recycle policy. Biowaste biorefinery systems in circular economy was discuss. Abstract: With the huge energy demand inevitably exacerbates the non-renewable resources depletion and ecological-social challenges, renewable energy has become a crucial participant in sustainable strategy. Biorefinery emerged as a sustainable approach and recognized promising transformation platforms for products, to achieve circular bioeconomy which focuses on the biomass efficient and sustainable valorization, promotes resource regeneration and restorative. The emerged biowaste biorefinery has proved as sustainable approach for integrated bioproducts and further applied this technology in industrial, commercial, agricultural and energy sectors. Based on carbon neutral sustainable development, this review comprehensive explained the biowaste as renewable resource generation and resource utilization technologies from the perspective of energy, nutrient and material recovery in the concept of biorefinery. Integrate biorefinery concepts into biowaste management is promise for conversion biowaste into value-added materials and contribute as driving force to cope with resource scarcity, climate changes and huge material demand in circular bioeconomy. In practice, the optimal of biorefinery technologies depends on environmentally friendly, economic and technical feasibility, social and policy acceptance. Additionally, policy interventions are necessary to promote biowaste biorefinery implements for circular bioeconomy and contribute to low-carbon cleaner environment.